IEEE Winter Conference on Applications of Computer Vision 2014
DOI: 10.1109/wacv.2014.6836058
|View full text |Cite
|
Sign up to set email alerts
|

Image segmentation of mesenchymal stem cells in diverse culturing conditions

Abstract: Researchers in the areas of regenerative medicine and tissue engineering have great interests in understanding the relationship of different sets of culturing conditions and applied mechanical stimuli to the behavior of mesenchymal stem cells (MSCs). However, it is challenging to design a tool to perform automatic cell image analysis due to the diverse morphologies of MSCs. Therefore, as a primary step towards developing the tool, we propose a novel approach for accurate cell image segmentation. We collected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Hence, global thresholding cannot be effective for segmentation purpose, making it essential to extract local areas to reduce the complexity of thresholding. To do so, variance in intensity of cell in the image and variance in intensity of background pixels can be measured as cell-pixel variance V c and backgroundpixel variance V b respectively, to quantify the complexity which arises from intensity variation 31 . The high value of either V c or V b or both shows the overlapping in the cell and background intensities, thereby increasing the difficulty or complexity in the segmentation process.…”
Section: Global Versus Local Thresholdingmentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, global thresholding cannot be effective for segmentation purpose, making it essential to extract local areas to reduce the complexity of thresholding. To do so, variance in intensity of cell in the image and variance in intensity of background pixels can be measured as cell-pixel variance V c and backgroundpixel variance V b respectively, to quantify the complexity which arises from intensity variation 31 . The high value of either V c or V b or both shows the overlapping in the cell and background intensities, thereby increasing the difficulty or complexity in the segmentation process.…”
Section: Global Versus Local Thresholdingmentioning
confidence: 99%
“…For defining the threshold, these approaches have exploited different features of the image as mentioned. Out of all these various approaches, it has been found that the approaches giving results close to the true value are Huang, Li and BEAS, with the BEAS being the most effective than other two 31 . Furthermore, BEAS method is reportedly having more advantages and reliability than many automated methods such as Fast Fourier Transform-Radial Sum 38 (FFTRS) and gradient-based approaches 39 .…”
Section: Thresholdingmentioning
confidence: 99%
See 2 more Smart Citations
“… 23 25 It has also been integrated with the study of histological tumor sections, 26 boundary detection of epithelial cell nuclei, 27 , 28 or understanding drug influences. 29 Image-based segmentation of MSCs reported previously 30 demonstrated better results compared to conventional thresholding techniques. However, this work was more driven toward identifying all cell regions rather than individual cells, making it unsuitable for culture quality monitoring through morphological profiling of each cell.…”
Section: Introductionmentioning
confidence: 95%